Methods for determining the hardness of materials : Book 1 : Macro range : laboratory works No. 1-12 - Moshchenok, Vasyl I.; Lalazarova, Nataliia; Moshchenok, Vasyl V. (GlobeEdit, 2024)
The textbook presents 12 laboratory works on determining the surface, projection and volume hardness of metals measured using classical Brinell, Rockwell and Vickers hardness targets. Each paper represents a complete scientific study that allows us to significantly extend the functionality of modern hardness testers. For each method, the corresponding formulas have been developed and tested, and the research methodology has been described in detail. These laboratory works are primarily aimed at postgraduate students and students of technical educational institutions, but can also be used in metallurgical production and mechanical engineering to assess the quality of products using hardness testing methods. All of the works have been tested over the past 10 years, have gained positive experience and can be recommended for active implementation in the educational process of technical universities.